#TITLE_ALTERNATIVE# - FAJRI (NIM 12204036); Pembimbing : Dr. Ir. Leksono Mucharram, M.Sc., INDRA
Uniform field as an oil and gas field which located in north Java Sea has been produce since 1972. In time of reached on pick production on 1975 the production is being decline because of the surface facilities are being old. The bad performance affected by pipe erosion, bottleneck due to scaling along pipe, and malfunction of separation facility in several Platforms which consequence high pressure loss along pipa and give any back pressure to another line. Because of that, it could increase pressure loss along pipe which decreases the productivity. So that, there are some study to evaluate lost production because of high pressure lost along pipe. Pipeline study at Uniform field use pipesim simulator which can integrate gas and oil line so that problem analysis can be determine integrately. So, it may develop some optimization strategies which cure all any problem which found and do improvisation scenario to have optimum oil and gas rate.